2015
DOI: 10.5352/jls.2015.25.9.1014
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Materials and Antioxidant Properties of Fermented Rice-bran Extract

Abstract: This study suggests that fermented rice bran extract contains natural antioxidants. The contents of bioactive materials (e.g., polyphenolic compounds and flavonoids), antioxidative properties (DPPH (α,α'-diphenyl-β-picrylhydrazyl) free radical scavenging activity, Fe reducing, Cu reducing power, peroxidation of linoleic acid and rat hepatocyte microsome) were tested by in vitro experimental models using fermented rice bran (FRB) extract. The concentrations of phenolic compound and flavonoid were 19.92 mg/g and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In our preliminary in vitro experiment, we compared the total amount of phenolic compounds and flavonoids, the degree of free radical-scavenging activity, the effects in inhibiting lipid peroxidation in liver microsome and the antioxidative effects between the FRB and the FRS. Thus, we found that the FRB had significantly better findings compared with the FRS [36].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In our preliminary in vitro experiment, we compared the total amount of phenolic compounds and flavonoids, the degree of free radical-scavenging activity, the effects in inhibiting lipid peroxidation in liver microsome and the antioxidative effects between the FRB and the FRS. Thus, we found that the FRB had significantly better findings compared with the FRS [36].…”
Section: Introductionmentioning
confidence: 52%
“…For the current experiment, we used active constituents of the FRB and FRS, both of which were provided by the Korea Bio-Solutions Co. Ltd. (Busan, Korea). The FRB was characterized in our previous study; the RB was fermented using Bacillus subtilis [36]. The FRS was the RSE ® (DuhanBio Co., Ltd., Seoul, Korea).…”
Section: Experimental Setting and Designmentioning
confidence: 99%